2015
DOI: 10.1021/acs.jpca.5b08003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Packing Patterns in Crystals by Analysis of Small Aggregates: A Case Study of CS2

Abstract: The molecular electrostatic potential (MESP) of the CS2 molecule, in conjunction with the cluster building algorithm, is utilized for generating trial geometries of medium-sized (CS2)n (n = 5-8) aggregates. MESP features suggest crossed, parallel stacked, T-shaped and L-shaped geometries for CS2 clusters. These initial geometries are subjected to geometry optimization employing second-order Møller-Plesset (MP2) theory, with correlation consistent aug-cc-pvDZ (aDZ) basis set. Single-point energies at MP2/aTZ le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The carbon quadrupole moment is negative, reflecting a reduced π-electron density around the C atom [196]. Because of this nature of the molecule, Singh et al [281] found that the molecule displays versatile coordination modes, and has ability to feature crossed, parallel-stacked, T-shaped, and L-shaped geometries in its clusters. This ability of the molecule explains why CS 2 could displays a number of coordination modes to form the hexabromofullerene carbon disulfide crystal.…”
Section: Examples Of Some Crystalmentioning
confidence: 99%
“…The carbon quadrupole moment is negative, reflecting a reduced π-electron density around the C atom [196]. Because of this nature of the molecule, Singh et al [281] found that the molecule displays versatile coordination modes, and has ability to feature crossed, parallel-stacked, T-shaped, and L-shaped geometries in its clusters. This ability of the molecule explains why CS 2 could displays a number of coordination modes to form the hexabromofullerene carbon disulfide crystal.…”
Section: Examples Of Some Crystalmentioning
confidence: 99%
“…The dimer forms a cross with a D 2d symmetry, 74 the trimer forms a pinwheel with a D 3 symmetry, 75 and the tetramer forms a barrel with a D 2d symmetry, 76 in general agreement with theoretical calculations. 77,78 Clusters containing more than 4 monomers are predicted to converge to the crystal structure, 79 orthorhombic 80 containing CS 2 pairs. The diffraction profile of small CS 2 clusters formed in superfluid helium droplets is shown in Fig.…”
Section: Examplesmentioning
confidence: 99%